Pengaruh Globalisasi terhadap Pembangunan Ekonomi di Negara Berkembang - Muhammad Azy Rahmanda Lubis; Fahmil Fadillah; Gunawan Prasetio; Khairina Tambunan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to analyze the impact of globalization on economic development in developing countries, focusing on both its positive and negative effects. Globalization has accelerated the integration of the global economy, enabling developing countries to access global markets, advanced technologies, and foreign direct investment (FDI). On the other hand, globalization also presents challenges such as economic inequality, dependency on developed nations, and resource exploitation. Using a qualitative approach with a literature review method, this study explores various data and literature from scientific journals, international organization reports, and related publications. The findings reveal that globalization significantly contributes to economic growth in developing countries through increased international trade, technology transfer, and job creation. However, these effects are not evenly distributed across sectors and social groups, leading to income disparities and uneven development. Furthermore, globalization pressures often push developing countries to adopt economic policies that are less supportive of local sectors, reducing domestic economic competitiveness. This study recommends the importance of balanced and sustainable development-oriented policies to maximize the benefits of globalization while minimizing its adverse impacts. Thus, developing countries can optimize globalization’s potential as a tool for inclusive and sustainable economic development.